An Old Assyrian Incantation against the Evil Eye - Barjamovic, Gojko (Altorientalische Forschungen, 2009)
A new Old Assyrian incantation against the evil eye ( ēnum lamuttum ) is published here, adding to the steadily increasing number of such texts. Parallels to Old Babylonian examples are provided, and in the context of a discussion of the religious life and practice of the Old Assyrian merchants, other new texts from Kültepe with previously unattested gods and information concerning a private chapel are presented.